Obesity mechanism after hypothalamic damage: Cohort analysis of neuroimaging, psychological, cognitive, and clinical phenotyping data - Lee, Miwoo; Park, Min-Jung; Lee, Kyung Hwa; Kim, Jung Hee; Choi, Hyung Jin; Kim, Yong Hwy (Frontiers in Endocrinology, 2023)
Objective: The hypothalamus regulates energy homeostasis, and its damage results in severe obesity. We aimed to investigate multifaceted characteristics of hypothalamic obesity. Methods: We performed multi-dimensional analyses of brain structure/function, psychological, and behavioral phenotypes in 29 patients with hypothalamic damage (HD) (craniopharyngioma) and 31 controls (non-functional pituitary adenoma). Patients underwent structural and functional magnetic resonance imaging and completed self-reports and cognitive tasks. Results: Patients with HD showed significantly higher postoperative weight gain than controls. HD group also showed significant hypothalamic damage, lower neural activation in the left caudate nucleus in response to food images. HD group had significantly higher food inattention, lower satiety, and higher restrained eating behavior.Within the HD group. higher restrained eating behavior was significantly associated with lower activation in the bilateral fusiform gyrus. Conclusions: These results suggest that hypothalamic damage contributes to weight gain by altering the brain response, attention, satiety, and eating behaviors. The present study proposes novel neuro-psycho-behavioral mechanisms targeted for patients with hypothalamic obesity.